2018
DOI: 10.1093/rheumatology/key188
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for refractory interstitial lung diseases in anti-melanoma differentiation-associated 5 gene antibody-positive dermatomyositis

Abstract: Combination therapy with TOF might have the potential to control refractory anti-MDA5 Ab+ DM-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
3
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(171 citation statements)
references
References 12 publications
5
140
3
7
Order By: Relevance
“…Our study has revealed a high prevalence of ILD inanti-MDA5 positive patients, consistentwith previous studies in Europeans and Japanese [2,20]. The short-term mortality rate of anti-MDA5 positive patients was especially high within the rst 6-12 months [5,9,13]. Based on these ndings, we set to analyze the rst six months living situation and identify the predictive factors for death in anti-MDA5 positive patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study has revealed a high prevalence of ILD inanti-MDA5 positive patients, consistentwith previous studies in Europeans and Japanese [2,20]. The short-term mortality rate of anti-MDA5 positive patients was especially high within the rst 6-12 months [5,9,13]. Based on these ndings, we set to analyze the rst six months living situation and identify the predictive factors for death in anti-MDA5 positive patients.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, in the studycontaining all types of myositis, anti-MDA5 has such a strong association with poor prognosis, that it dominates the analysis and makes other potential poor prognostic factors even tendto be a protective factor [11]. While in the subgroup of anti-MDA5 positive patients, the reported risk factors varied in different reports, possibly due to small sample size [5,9,13].…”
Section: Risk Factors Predicting Poor Prognosis Have Been Establishedmentioning
confidence: 97%
See 1 more Smart Citation
“…On the faith of a small case series of four patients, basiliximab, a monoclonal antibody targeting CD25+ activated T cells, could improve patients' survival (105). Similarly, JAK-inhibitors (in this case tofacitinib), which blocks interferon pathways and other proinflammatory cytokine pathways, has shown a promising survival rate improvement (17,106).…”
Section: Biologicsmentioning
confidence: 99%
“…Of note, in the study containing all types of myositis, anti-MDA5 has such a strong association with poor prognosis, that it dominates the analysis and makes other potential poor prognostic factors even tend to be a protective factor [11]. While in the subgroup of anti-MDA5 positive patients, the reported risk factors varied in different reports, possibly due to small sample size [5,9,13].…”
Section: Risk Factors Predicting Poor Prognosis Have Been Establishedmentioning
confidence: 97%